Filtration-induced production of conductive/robust Cu films on cellulose paper by low-temperature sintering in air - Shintaro Sakurai; Yusuke Akiyama; Hideya Kawasaki (Royal Society Open Science, 2018)
Cellulose paper is an attractive substrate for paper electronics because of its advantages of flexibility, biodegradability, easy incorporation into composites, low cost and eco-friendliness. However, the micrometre-sized pores of cellulose paper make robust/conductive films difficult to deposit onto its surface from metal-nanoparticle-based inks. We developed a Cu-based composite ink to deposit conductive Cu films onto cellulose paper via low-temperature sintering in air. The Cu-based inks consisted of a metallo-organic decomposition ink and formic-acid-treated Cu flakes. The composite ink was heated in air at 100°C for only 15 s to give a conductive Cu film (7 × 10−5 Ω cm) on the cellulose paper. Filtration of the Cu-based composite ink accumulated Cu flakes on the paper, which enabled formation of a sintered Cu film with few defects. A strategy was developed to enhance the bending stability of the sintered Cu films on paper substrates using polyvinylpyrrolidone-modified Cu flakes and amine-modified paper. The resistance of the Cu films increased only 1.3-fold and 1.1-fold after 1000 bending cycles at bending radii of 5 mm and 15 mm, respectively. The results of this study provide an approach to increasing the bending stability of Cu films on cellulose paper.